2004
DOI: 10.2188/jea.14.73
|View full text |Cite
|
Sign up to set email alerts
|

The Estimated Prevalence of Hypospadias in Hokkaido, Japan

Abstract: BACKGROUND: Hypospadias is one of the most common congenital anomalies in the world. Recently, increases in the prevalence of hypospadias have been reported in various countries including Japan. In this study, we examined whether the prevalence of hypospadias in Hokkaido, Japan, increased or not, using standardized diagnostic criteria. We also investigated the degree of its severity. METHODS: We calculated prevalence of hypospadias using hospital records of hypospadias repair in Hokkaido. The preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 25 publications
0
38
0
Order By: Relevance
“…In northern England, the birth prevalence increased at a rate of 0.05 per 1000 male live births per year between 1993 and 2000 (Abdullah et al 2007a). However, reports from Scotland for 1988 to 1997 (Ahmed et al, 2004), New York for 1992-2005(Fisch et al, 2009), California for 1989to 1997(Carmichael et al, 2003, Washington for 1987 to 2002 (Porter et al, 2005), and Hokkaido, Japan for 1985 to 1997 (Kurahashi et al, 2004) did not indicate any growth trends in prevalence rates.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In northern England, the birth prevalence increased at a rate of 0.05 per 1000 male live births per year between 1993 and 2000 (Abdullah et al 2007a). However, reports from Scotland for 1988 to 1997 (Ahmed et al, 2004), New York for 1992-2005(Fisch et al, 2009), California for 1989to 1997(Carmichael et al, 2003, Washington for 1987 to 2002 (Porter et al, 2005), and Hokkaido, Japan for 1985 to 1997 (Kurahashi et al, 2004) did not indicate any growth trends in prevalence rates.…”
Section: Discussionmentioning
confidence: 93%
“…Currently, the time trends of hypospadias prevalence in other countries worldwide are not consistent. Australia (Nassar et al, 2007), Denmark (Lund et al, 2009), and the United Kingdom (Abdullah et al, 2007a) have reported increasing trends in hypospadias prevalence, whereas Japan (Kurahashi et al, 2004), Scotland (Ahmed et al, 2004), and the U.S. states of New York (Fisch et al, 2009), Washington (Porter et al, 2005), and California (Carmichael et al, 2003) have reported no significant increases. In addition, regional differences in hypospadias prevalences have been reported; for example, a spatial clustering of hypospadias prevalences was found in northern England (Abdullah et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…Hypospadias is a common congenital malformation that is readily recognized at birth. Epidemiological studies conducted worldwide report a prevalence rate within the range of 0.4 -0.8 per 1000 births (303)(304)(305)(306). Denmark has a particularly high birth prevalence of 10 per 1000 births, which increased later to a level of 46 per 1000 births when additional mild cases were found after the foreskin could be retracted (307).…”
Section: Reproductive Tract Abnormalitiesmentioning
confidence: 99%
“…[1][2][3][4] The etiology of hypospadias is likely a combination of genetic and environmental factors [5,6] , but precise gene candidates have been elusive.…”
Section: Introductionmentioning
confidence: 99%